2016
DOI: 10.3803/enm.2016.31.2.320
|View full text |Cite
|
Sign up to set email alerts
|

C-Peptide-Based Index Is More Related to Incident Type 2 Diabetes in Non-Diabetic Subjects than Insulin-Based Index

Abstract: BackgroundDiabetes can be efficiently prevented by life style modification and medical therapy. So, identification for high risk subjects for incident type 2 diabetes is important. The aim of this study is to identify the best β-cell function index to identify high risk subjects in non-diabetic Koreans.MethodsThis is a retrospective longitudinal study. Total 140 non-diabetic subjects who underwent standard 2-hour 75 g oral glucose tolerance test from January 2007 to February 2007 at Kangbuk Samsung Hospital an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 27 publications
2
47
1
Order By: Relevance
“…Previous studies showed citrus flavonoids positively regulate adiponectin transcription in adipocytes and increase their levels in patients with myocardial infarction (Haidari et al, ; Liu et al, ). These data corroborate with our findings, where supplementation with Eriomin increased serum adiponectin levels by 18% and reduced the concentration of C‐peptide by 5%, an important marker of beta cell function that allows differentiation between the prognosis of type 1 and type 2 diabetes (Kim et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies showed citrus flavonoids positively regulate adiponectin transcription in adipocytes and increase their levels in patients with myocardial infarction (Haidari et al, ; Liu et al, ). These data corroborate with our findings, where supplementation with Eriomin increased serum adiponectin levels by 18% and reduced the concentration of C‐peptide by 5%, an important marker of beta cell function that allows differentiation between the prognosis of type 1 and type 2 diabetes (Kim et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…CPI is more accurate predictive beta cell function than C-peptide measurements (Kim et al 2016). Furthermore, if significant hyperglycemia persists, C-peptide levels may also be found to be lower than normal due to glucose toxicity (Jones and Hattersley 2013).…”
Section: Discussionmentioning
confidence: 98%
“…That study concluded that elevated c-peptide was one of the important risk factor for diabetes. 9 Study done by Thazin et al in Myanmar quoted that increased fasting c-peptide was significantly associated with prediabetes. 13 Though microalbuminuria and elevated c-peptide were prevalent in our study population, none of the study participants had fundus retinopathic changes.…”
Section: Discussionmentioning
confidence: 99%
“…8 There were some reports that C-peptide-based indices were better indices than insulin based indices for the evaluation of pathophysiology of diabetes. 9 According to National Kidney Foundation, microalbuminuria defined as "urine albumin excretion rate of approximately 30-300 mg/dl in at least two of three consecutive samples of non-ketotic sterile urine.…”
Section: Introductionmentioning
confidence: 99%